Culture of Cutaneous Leishmania from Skin Biopsy Specimens. Issue 2 (19th February 2022) - Paun, Andrea
Abstract: This protocol describes the culture of Leishmania parasites from skin biopsy samples of patients with cutaneous lesions. The use of antibiotics to prevent bacterial contamination of these cultures increases the ability of researchers to collect isolates for various research purposes, including genetic analysis and in vitro and in vivo experiments. © Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol : Culture of Leishmania from skin biopsy specimens.